PEMBELAJARAN AL-NAá¸¤WU TERAPAN (APLIKASI DASAR-DASAR AL-NAá¸¤WU BAGI PEMULA) - Usman Husein (Universitas Islam Negeri Ar-Raniry, 2013)
Al-naá¸¥wu is often claimed as a difficult material in Arabic Instruction, not only for beginners but also for those who have learned it for years. It is probably caused by the habit of memorizing the terminology of Al-naá¸¥wu without knowing how to use it. Besides, there are some exceptions related to al-naá¸¥wu to be memorized by the user of the language. This article will explain about how to design and teach effectively al-naá¸¥wu to the students to ease the learner to use it.